Calcium-based composite flocculant based on SiO2 micro powder as well as preparation method and application of calcium-based composite flocculant
Through the preparation method of calcium-based composite flocculant, the problems of SiO2 fine powder solid waste treatment and resource utilization are solved, and the flocculation effect with simple process and significant effect is achieved, which is suitable for wastewater purification and treatment.
Patent Information
- Application Number
- CN202411454879.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-27
AI Technical Summary
There are difficulties in the treatment and resource utilization of SiO2 micropowder solid waste, the existing technology is complex and the economic benefits are poor, and the complexity of impurity components of SiO2 micropowder leads to its low activity and difficult to effectively utilize.
The preparation method of calcium-based composite flocculant based on SiO2 micropowder is adopted to form a polysilicate solution by heating reaction of inorganic strong alkali aqueous solution. After maturation, activation and standing, polyaluminum silicate flocculant is formed, and reacted with CaO to form a calcium-based composite Flocculant.
It realizes the resource-based treatment and resource-based utilization of SiO2 micropowder solid waste. It has simple process, convenient operation, good flocculation effect, and can effectively remove Fe3+, nano-oil beads in wastewater and reduce COD.
Smart Images

Figure CN119191504A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of solid waste treatment, and in particular to a calcium-based composite flocculant based on SiO2 micropowder, and a preparation method and application thereof. Background Art
[0002] SiO2 is an important raw material in the production process of high-end products such as photovoltaic cells and chips. In the industrial production process, SiO2 smoke will be generated, which will be condensed into fine spherical micro-bead dust by cooling. After being collected by dust collection facilities, SiO2 micro-powder is obtained. The particle size of this type of SiO2 micro-powder is generally 0.1-150μm, and the composition is relatively complex. In addition to SiO2, it also contains impurities such as elemental silicon, hydrochloric acid, and CaCl2, which is a kind of solid waste. Generally speaking, the condensation process of SiO2 smoke is so rapid that SiO2 has no time to form crystals. Therefore, most of the SiO2 micro-powder is amorphous and belongs to amorphous minerals. This type of SiO2 micro-powder solid waste has a low density, extremely fine particles, and a low silicon content. Large amounts of accumulation not only take up space, but also easily enter the atmosphere to become inhalable particles, seriously affecting the health of workers and nearby residents. Therefore, the harmless treatment of SiO2 micro-powder solid waste is of great significance.
[0003] Since there are many types of impurities and different impurity contents in SiO2 micropowder solid waste, the initial investment for fine purification is large and the profit margin is low. Therefore, enterprises generally outsource it for disposal as solid waste. In the existing recycling and treatment technologies, the scale is generally small, and the pollutants generated during the recycling and treatment process are difficult to treat, the economic benefits are not obvious, and it is even difficult to achieve the purpose of profit. Therefore, the development momentum of the SiO2 micropowder solid waste treatment market is not great. In addition, the country has not yet issued relevant policies on the resource utilization of SiO2 solid waste. In the absence of incentives and support from relevant policies, most companies are in a wait-and-see state.
[0004] There have been a lot of studies at home and abroad on the resource utilization of silicon-containing industrial solid waste. For example, SiO2 micropowder solid waste is mixed with cement as concrete to achieve the recycling of SiO2 micropowder solid waste, but the quality of SiO2 micropowder varies, and the effect on the performance of cement-based materials is unstable. Coupled with the shrinkage of construction projects in recent years, the benefits of this treatment method are minimal. Water is added to SiO2 micropowder solid waste to make pellets with a diameter of 10 to 50 mm, sintered at high temperature, and used as raw materials for electric furnaces. This treatment method can only dispose of SiO2 micropowder as solid waste, and the valuable silicon resources cannot be effectively utilized. SiO2 micropowder solid waste replaces pure alumina mud and is mixed into refractory products as an additive and binder to improve the high temperature resistance of the product. However, SiO2 micropowder is used as an auxiliary material in a small amount and cannot achieve the absorption of a large amount of SiO2 micropowder. In addition, SiO2 micropowder is also used as an additive for insulating materials, electronic industrial materials, and dispersing and isolating agents for chemical products. However, these uses have high requirements on the quality of SiO2 micropowder, requiring the SiO2 micropowder to reach electrical grade. Conventional SiO2 micropowder solid waste is difficult to reach this level, which limits its secondary utilization.
[0005] The preparation of silicate flocculants using silicon as raw material is a hot topic of research. At present, fly ash solid waste is subjected to the action of strong alkali to break the Si-O and Al-O bonds in the fly ash, wherein SiO2 is converted into silicate molecules, and then gradually forms branched, cyclic or network silica gel flocculants through self-polymerization reaction. The single-molecule silica gel flocculant can play a flocculation role by utilizing its pore size adsorption characteristics. However, there are only reports on SiO2 in fly ash solid waste as a flocculant. Compared with SiO2 in fly ash solid waste, the situation of SiO2 micropowder solid waste is more complicated. It contains hydroxyl groups on its surface and has strong water solubility and activity. Therefore, it is easy to produce by-products in the polymerization reaction. The presence of the by-products will affect the purity of the prepared polymer, and then affect the flocculation effect. In addition, due to the effect of hydrogen bonds formed between hydroxyl groups, the nanoparticles in SiO2 micropowder always exist in the form of agglomerates. The activity of SiO2 micropowder in this form is lower, making it difficult to treat SiO2 micropowder solid waste using the same method.
[0006] In summary, the resource utilization of SiO2 micropowder solid waste is of great significance. Among them, using it as a raw material for preparing silicate flocculants is a more preferred harmless treatment method. However, the research on the preparation of flocculants using SiO2 micropowder solid waste is not mature enough. Therefore, a method with simple process and convenient operation is urgently needed to use SiO2 micropowder solid waste to prepare flocculants, so that it can not only meet the needs of resource treatment of SiO2 micropowder solid waste, but also realize the resource utilization of SiO2 micropowder solid waste. Summary of the invention
[0007] The main purpose of the present invention is to solve the problem of SiO2 micropowder solid waste treatment and the resource utilization problem of SiO2 micropowder solid waste.
[0008] In order to solve the above problems, the present invention provides a method for preparing a calcium-based composite flocculant based on SiO2 micropowder, and the preparation method comprises the following steps: step (1), adding an inorganic strong alkali aqueous solution to SiO2 micropowder, heating to react, and obtaining a polysilicate solution; wherein the SiO2 micropowder is SiO2 micropowder solid waste; step (2), aging, activating, and standing the polysilicate solution at a constant temperature to obtain a polysilicic acid solution; step (3), adding aluminum sulfate to the polysilicic acid solution, stirring and mixing, and then adjusting the pH and aging to obtain a polysilicate aluminum flocculant; step (4), adding CaO to the polysilicate aluminum flocculant to obtain a calcium-based composite flocculant.
[0009] Furthermore, the SiO2 content in the SiO2 micropowder solid waste is 90-99wt%; preferably, the particle size of the SiO2 micropowder is 0.1-150μm.
[0010] Furthermore, in terms of weight ratio, the amount of CaO added in step (4) is 1 to 1.3 times the SiO2 content in the SiO2 micropowder; preferably, in terms of weight ratio, the amount of aluminum sulfate added in step (3) is 1.5 to 3 times the SiO2 content in the SiO2 micropowder; more preferably, in terms of weight ratio, the amount of aluminum sulfate added in step (3) is 2 to 3 times the SiO2 content in the SiO2 micropowder.
[0011] Furthermore, the aqueous solution of the inorganic strong alkali is an aqueous solution of NaOH and / or KOH; preferably, the concentration of the aqueous solution of the inorganic strong alkali is 1 to 2 mol / L; preferably, the molar amount of the inorganic strong alkali in step (1) is 1 to 3 times the molar amount of SiO2 in the SiO2 micropowder; preferably, the temperature of the heating reaction in step (1) is 70 to 75°C, and the time is 150 to 300 min.
[0012] Furthermore, in step (2), the aging is achieved by adding a strong inorganic acid to the polysilicate solution to adjust the pH; preferably, the strong inorganic acid is sulfuric acid and / or hydrochloric acid; preferably, the concentration of the strong inorganic acid is 1 to 4 mol / L; preferably, the pH is adjusted to 2.5 to 4.0 during the aging operation; more preferably, the pH is adjusted to 3.2 to 3.5 during the aging operation.
[0013] Furthermore, the activation operation is achieved by heating and stirring the matured polysilicate solution; preferably, the heating temperature during activation is 40-60°C, the time is 70-100 min, and the stirring speed is 300-350 rpm; further preferably, the activation time is 85-95 min.
[0014] Furthermore, in step (2), the temperature of the constant temperature standing is 40 to 60° C., and the time is 1.5 to 2.5 hours.
[0015] Furthermore, the stirring time after adding aluminum sulfate in step (3) is 20 to 30 minutes; preferably, the pH is adjusted to 1.6 to 1.7 in step (3); preferably, the aging time in step (3) is 2.5 to 3.5 hours; preferably, the stirring time after adding CaO in step (4) is 2 to 4 minutes.
[0016] According to another aspect of the present invention, a calcium-based composite flocculant based on SiO2 micropowder is also provided. The calcium-based composite flocculant is prepared by the above-mentioned preparation method.
[0017] According to a third aspect of the present invention, there is also provided an application of the above-mentioned calcium-based composite flocculant based on SiO2 micropowder, wherein the calcium-based composite flocculant is used for purifying wastewater.
[0018] The present application provides a method for preparing a calcium-based composite flocculant based on SiO2 micropowder. The preparation method first obtains effective SiO2 in SiO2 micropowder solid waste by alkaline leaching extraction, and then forms polysilicic acid and polyaluminum silicate flocculants in turn through a series of operations, and finally composites with calcium to obtain a calcium-based composite flocculant. The flocculant can use SiO2 micropowder solid waste as a raw material for preparing a calcium-based composite flocculant, which can not only meet the needs of resource treatment of SiO2 micropowder solid waste, but also realize the resource utilization of SiO2 micropowder solid waste. In addition, the preparation method has a simple process and is easy to operate, and is very effective in removing Fe from wastewater. 3+ It has a good effect on removing nano oil droplets and reducing COD. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0020] Figure 1 The FTIR graphs of the calcium-based composite flocculants prepared in Examples 1, 6 and 7 of the present invention are shown;
[0021] Figure 2 The graph shows the COD of different batches of sewage before treatment and the COD of sewage after treatment when the calcium-based flocculant composite prepared in Example 1 is applied to factory sewage treatment;
[0022] Figure 3 To test Fe 3+ The standard curve was drawn at the concentration. DETAILED DESCRIPTION
[0023] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0024] As described in the background technology section, the preparation of silicate flocculants based on SiO2 micropowder solid waste as raw materials is a more preferred harmless treatment method for treating SiO2 micropowder solid waste. However, the composition of SiO2 micropowder solid waste is complex, and the presence of hydroxyl groups on its surface will not only affect the purity of the flocculant, but also the action of hydrogen bonds formed between hydroxyl groups will make the nanoparticles in the SiO2 micropowder always exist in the form of agglomerates. The activity of SiO2 micropowder in this form is lower, and the effect of using SiO2 micropowder solid waste to prepare flocculants is not good. Therefore, there is an urgent need for an effective, simple process, and convenient operation method to use SiO2 micropowder solid waste to prepare flocculants, so that it can not only meet the needs of resource treatment of SiO2 micropowder solid waste, but also realize the resource utilization of SiO2 micropowder solid waste.
[0025] In order to solve the above problems, the present invention proposes a method for preparing a calcium-based composite flocculant based on SiO2 micropowder, which comprises the following steps: step (1), adding an inorganic strong alkali aqueous solution to SiO2 micropowder, heating to react, and obtaining a polysilicate solution; wherein the SiO2 micropowder is SiO2 micropowder solid waste; step (2), subjecting the polysilicate solution to aging, activating, and constant temperature standing to obtain a polysilicic acid solution; step (3), adding aluminum sulfate to the polysilicic acid solution, stirring and mixing, and then adjusting the pH and aging to obtain a polysilicate aluminum flocculant; step (4), adding CaO to the polysilicate aluminum flocculant to obtain a calcium-based composite flocculant.
[0026] The method firstly utilizes an inorganic strong alkali aqueous solution to decompose effective SiO2 components in SiO2 micropowder solid waste, and further reacts it by heating reaction to obtain a polysilicate solution; then the polysilicate solution is subjected to a series of operations such as aging, activation, and constant temperature standing in sequence to obtain a polysilicic acid solution; then aluminum sulfate is added to the polysilicic acid solution and stirred and mixed, and the solution is aged by adjusting the pH value and by standing precipitation to allow it to fully react to obtain a polysilicate aluminum flocculant; finally, the polysilicate aluminum flocculant is mixed with CaO to graft the calcium ions in the polysilicate aluminum flocculant and the CaO to obtain a calcium-based composite flocculant.
[0027] Solid wastes come from a wide range of sources, including semiconductor manufacturing, solar cell manufacturing, or the production of fly ash and calcined coal gangue. Therefore, there are many types of impurities and different impurity contents. In addition to SiO2, SiO2 micropowder solid wastes may contain at least one impurity of elemental silicon, hydrochloric acid, and CaCl2, or one or more impurities such as carbon powder, stone powder, and Al2O3. The preparation method of calcium-based composite flocculant based on SiO2 micropowder described in this application does not require the types of impurities in SiO2 micropowder solid wastes and the effective content of SiO2 therein, and is naturally applicable to SiO2 micropowders with an effective content of 100%.
[0028] In particular, the present application first decomposes the effective SiO2 component in the SiO2 micropowder solid waste by using an inorganic strong alkali aqueous solution, and then obtains a polysilicate solution by heating reaction. SiO2 micropowder solid waste generally contains more impurities, and the types of impurities are different. Therefore, the effective SiO2 component in the SiO2 micropowder solid waste is first decomposed by an alkali leaching method, thereby forming a polysilicate solution with an inorganic strong alkali aqueous solution. In addition, in some SiO2 micropowder solid wastes, due to the effect of hydrogen bonds formed between hydroxyl groups on the surface, the nanoparticles in the SiO2 micropowder therein always exist in the form of agglomerates. The SiO2 micropowder in this form has lower activity and is not effective for preparing flocculants. However, this problem can be effectively overcome by extracting with an alkali leaching method and coordinating with a series of subsequent ripening, activation and other operations. In addition, through a series of operations such as alkali leaching, aging, activation, and standing, the present invention can make the obtained polyaluminum silicate flocculant have a better degree of polymerization, and further make the obtained high-molecular calcium-based composite flocculant have a larger molecular weight and a better degree of polymerization. The calcium-based composite flocculant with a higher degree of polymerization can more easily play its bridging role and netting role in the flocculation process, and achieve a better flocculation effect.
[0029] Furthermore, the present application also obtains a calcium-based composite flocculant by mixing a polysilicate aluminum flocculant and CaO, and reacting the polysilicate aluminum flocculant and CaO. The polysilicate aluminum flocculant is further grafted with calcium ions, so that the flocculation performance of the polysilicate aluminum flocculant can be better regulated, so that the obtained calcium-based composite flocculant has a better flocculation effect. In addition, after a large number of experimental explorations, the inventors found that the calcium-based composite flocculant obtained by using CaO as a substance and the polysilicate aluminum flocculant can make the obtained calcium-based composite flocculant have better polymerization degree and flocculation performance. There are two reasons for this analysis: First, CaO reacts with water to generate Ca(OH)2, which is slightly soluble in water. After mixing with the polysilicate aluminum flocculant, it can further increase the demulsification effect, improve the grafting effect of calcium ions and the polysilicate aluminum flocculant, and improve the polymerization degree and flocculation performance of the calcium-based composite flocculant. Secondly, the reaction of CaO and water to generate Ca(OH)2 is an exothermic reaction, and the temperature in the system will rise slightly, which can further promote the grafting of calcium ions and polyaluminum silicate flocculants and improve the flocculation effect of the calcium-based composite flocculant.
[0030] In summary, the preparation method of the calcium-based composite flocculant based on SiO2 micropowder provided in this application can not only meet the demand for resource treatment of SiO2 micropowder solid waste, but also realize the resource utilization of SiO2 micropowder solid waste. Moreover, the calcium-based composite flocculant obtained by this method not only has a good degree of polymerization and a good flocculation effect, but also has the advantages of simple process and convenient operation.
[0031] In a preferred embodiment, the SiO2 content in the SiO2 micropowder solid waste is 90-99wt%; preferably, the particle size of the SiO2 micropowder is 0.1-150μm. Under the above conditions, the calcium-based composite flocculant prepared by the preparation method has better polymerization degree and flocculation effect.
[0032] In a preferred embodiment, the amount of CaO added in step (4) is 1 to 1.3 times the SiO2 content in the SiO2 micropowder by weight. The role of CaO is to provide calcium ions for grafting to the polysilicate aluminum flocculant to obtain a calcium-based composite flocculant. Therefore, when the amount of CaO added is 1 to 1.3 times the SiO2 content in the SiO2 micropowder, a good grafting effect can be achieved. Further, the amount of aluminum sulfate added in step (3) is controlled to be 1.5 to 3 times the SiO2 content in the SiO2 micropowder by weight. The ratio of SiO2 micropowder to aluminum sulfate will affect the flocculation effect of the calcium-based composite flocculant, mainly because: when the ratio of the two is low, it will affect the polymerization reaction rate of polysilicic acid and aluminum sulfate when forming the polysilicate aluminum flocculant, and will also affect the degree of polymerization, thereby affecting the structure and quality of the calcium-based composite flocculant. When the amount of aluminum sulfate added is 1.5 to 3 times the SiO2 content in the SiO2 micropowder, the product can achieve a better flocculation effect. More preferably, when the amount of aluminum sulfate added in step (3) is controlled to be 2 to 3 times the SiO2 content in the SiO2 micropowder by weight, the calcium-based composite flocculant product has a better flocculation effect.
[0033] In a preferred embodiment, the inorganic strong alkali aqueous solution is an aqueous solution of NaOH and / or KOH. The inorganic strong alkali aqueous solution is mainly used for alkali leaching extraction of the effective components in the SiO2 micropowder solid waste, so the NaOH aqueous solution and / or KOH aqueous solution have a better extraction effect. Preferably, the concentration of the inorganic strong alkali aqueous solution is 1-2 mol / L. When the concentration of the alkali solution is too low, the amount added needs to be increased when adjusting the pH, which will affect the concentration of the polysilicate solution and the concentration of the entire polymerization system in the subsequent preparation process. Controlling the concentration of the inorganic strong alkali aqueous solution to 1-2 mol / L can achieve better results. Preferably, the temperature of heating and stirring in step (1) is 70-75°C and the time is 150-300min. The above heating temperature and stirring time can better extract the effective components in the SiO2 micropowder solid waste. Preferably, the molar amount of the inorganic strong alkali in step (1) is 1-3 times the molar amount of SiO2 in the SiO2 micropowder. Controlling the amount of alkali added within the above range can better form a polysilicate solution.
[0034] In a preferred embodiment, the aging in step (2) is achieved by adding an inorganic strong acid to the polysilicate solution to adjust the pH; preferably, the inorganic strong acid is sulfuric acid and / or hydrochloric acid; preferably, the concentration of the inorganic strong acid is 1 to 4 mol / L. When the polysilicate solution is prepared into a polysilicic acid solution, it needs to undergo aging, activation and constant temperature standing operations, wherein the pH is adjusted with sulfuric acid and / or hydrochloric acid during aging, and the acid concentration is controlled to be 1 to 4 mol / L, so as to achieve the purpose of aging the polysilicate solution. Preferably, during the aging operation, the pH is adjusted to within the range of 2.5 to 4.0, which can achieve a good aging effect, which is beneficial to improving the quality of the calcium-based composite flocculant; more preferably, during the aging operation, the aging effect is better when the pH is adjusted to within the range of 3.2 to 3.5, and the flocculation performance and polymerization degree of the obtained calcium-based composite flocculant are also better. Too high a pH during aging will affect the subsequent polymerization effect of the flocculant and the grafting effect with cations, thereby affecting the flocculation performance of the flocculant.
[0035] In a preferred embodiment, the activation operation is achieved by heating and stirring the matured polysilicate solution. Preferably, the heating temperature during activation is 40-60°C, the time is 70-100 min, and the stirring speed is 300-350 rpm. Further activation of the matured silicic acid solution according to the above conditions can give the silicic acid solution a better polymerization effect. The better the polymerization effect, the larger the molecular weight of the flocculant formed subsequently, and the more conducive to the flocculation of the flocculant, which will have a beneficial effect on the subsequent formation of polysilicate, polysilicate aluminum flocculant and calcium-based composite flocculant. Further preferably, the activation time is controlled to be 85-95 min, which is conducive to the preparation of a better calcium-based composite flocculant.
[0036] In a preferred embodiment, the temperature of the constant temperature standing in step (2) is 40-60°C and the time is 1.5-2.5 hours. The silicic acid solution obtained after the polysilicate solution undergoes aging and activation operations is kept at a constant temperature so that the silicic acid solution in the system can be further polymerized to obtain a polysilicate solution. When the standing temperature and standing time are controlled under the above conditions, the polymerization effect of the silicic acid solution is better.
[0037] In a preferred embodiment, the stirring time after adding aluminum sulfate in step (3) is 20 to 30 minutes; preferably, the pH is adjusted to 1.6 to 1.7 in step (3); preferably, the aging time in step (3) is 2.5 to 3.5 hours. The purpose of adding aluminum sulfate to the polysilicic acid solution is to obtain a polysilicic acid aluminum flocculant. The polysilicic acid aluminum flocculant obtained has better effect by controlling the stirring time, reaction time and pH adjustment range of the polysilicic acid solution and aluminum sulfate within the above range. Preferably, the stirring time after adding CaO in step (4) is 2 to 4 minutes. The stirring time within the above range can achieve a good effect of grafting cations.
[0038] A calcium-based composite flocculant based on SiO2 micropowder, which is prepared using SiO2 micropowder solid waste as a raw material according to the above preparation method and has good polymerization degree and flocculation effect.
[0039] According to another aspect of the present invention, the application of the calcium-based composite flocculant prepared by the above preparation method is also provided. The calcium-based composite flocculant is used to purify wastewater, and the removal rate of COD in the wastewater can reach more than 77.5%, the removal rate of nano-oil droplets in the wastewater can reach more than 74%, and the removal rate of Fe 3+ The removal rate can reach more than 72%. Preferably, in the process of treating wastewater, the stirring speed is controlled at 300-400 rpm, at which time the removal rate of impurities in the wastewater is better.
[0040] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0041] It should be further explained here that the SiO2 fine powder solid waste used in Examples 1 to 9 and the comparative example is produced in the production process of single crystal silicon, the particle size of the SiO2 fine powder solid waste is 0.1-100 μm, the effective content of SiO2 is 95wt%, and the impurities contained are elemental silicon, hydrochloric acid and CaCl2. The SiO2 fine powder solid waste used in Example 10 is produced in the production of fly ash, the particle size of the SiO2 fine powder solid waste is 50-150 μm, the effective content of SiO2 is 90wt%, and the impurities contained are carbon powder and Al2O3. The SiO2 fine powder solid waste used in Example 11 comes from the production of calcined coal gangue, the particle size of the SiO2 fine powder solid waste is 30-150 μm, the effective content of SiO2 is 99wt%, and it contains stone powder and carbon powder impurities.
[0042] Example 1
[0043] Add 190 mL of 2 mol L -1 NaOH aqueous solution, stirred at 70 ° C for 300 min to obtain a sodium polysilicate solution; -1 The pH value of the sodium polysilicate solution was adjusted to 3.5 with an aqueous solution of sulfuric acid and then stirred at 50°C at a stirring speed of 350 rpm for 90 minutes to completely convert it into silicic acid and activate the silicic acid. Finally, it was kept at a constant temperature of 50°C for 2 hours to allow the activated silicic acid to gradually polymerize to obtain a polysilicate solution; 23.75 g of aluminum sulfate was added to the polysilicate solution and stirred for 20 minutes to mix it evenly, and then the pH value was adjusted to 1.6 and aged for 3 hours to obtain a polysilicate aluminum flocculant; 9.5 g of CaO was added to the polysilicate aluminum flocculant and stirred for 2 minutes to mix it evenly to obtain a calcium-based composite flocculant.
[0044] The calcium-based composite flocculant prepared in this example was subjected to FTIR testing, and the results are shown in Figure 1 .
[0045] Example 2
[0046] Add 150 mL of 1 mol L -1 The KOH aqueous solution was stirred at 75 °C for 150 min to obtain a potassium polysilicate solution; 4 mol L -1 The pH value of the sodium polysilicate solution was adjusted to 2.5 with an aqueous hydrochloric acid solution, and then the solution was stirred at 40°C at a stirring speed of 300 rpm for 100 min to completely convert it into silicic acid and activate the silicic acid. Finally, the solution was kept at a constant temperature of 60°C for 1.5 h to allow the activated silicic acid to gradually polymerize, thereby obtaining a polysilicate solution. 19 g of aluminum sulfate was added to the polysilicate solution and stirred for 30 min to mix it evenly, and then the pH value was adjusted to 1.7 and aged for 2.5 h to obtain a polysilicate aluminum flocculant. 12.35 g of CaO was added to the polysilicate aluminum flocculant and stirred for 2 min to mix it evenly, thereby obtaining a calcium-based composite flocculant.
[0047] Example 3
[0048] Add 250 mL of 2 mol L -1 NaOH aqueous solution, stirred at 70 ° C for 300 min to obtain a sodium polysilicate solution; -1 The pH value of the sodium polysilicate solution was adjusted to 4.0 with an aqueous solution of sulfuric acid and then stirred at 60°C at a stirring speed of 350 rpm for 70 minutes to completely convert it into silicic acid and activate the silicic acid. Finally, it was placed at a constant temperature of 40°C for 2.5 hours to allow the activated silicic acid to gradually polymerize to obtain a polysilicate solution; 19 g of aluminum sulfate was added to the polysilicate solution and stirred for 20 minutes to mix it evenly, and then the pH value was adjusted to 1.6 and aged for 3.5 hours to obtain a polysilicate aluminum flocculant; 9.5 g of CaO was added to the polysilicate aluminum flocculant and stirred for 4 minutes to mix it evenly to obtain a calcium-based composite flocculant.
[0049] Example 4
[0050] The difference from Example 1 is that the amount of aluminum sulfate added in step (3) is 3 times the SiO2 content in the SiO2 micropowder.
[0051] Add 190 mL of 2 mol L -1 NaOH aqueous solution, stirred at 70 ° C for 300 min to obtain a sodium polysilicate solution; -1The pH value of the sodium polysilicate solution was adjusted to 3.5 with an aqueous solution of sulfuric acid and then stirred at 50°C at a stirring speed of 350 rpm for 90 minutes to completely convert it into silicic acid and activate the silicic acid. Finally, it was kept at a constant temperature of 50°C for 2 hours to allow the activated silicic acid to gradually polymerize to obtain a polysilicate solution; 28.5 g of aluminum sulfate was added to the polysilicate solution and stirred for 20 minutes to mix it evenly, and then the pH value was adjusted to 1.6 and aged for 3 hours to obtain a polysilicate aluminum flocculant; 9.5 g of CaO was added to the polysilicate aluminum flocculant and stirred for 2 minutes to mix it evenly to obtain a calcium-based composite flocculant.
[0052] Example 5
[0053] The difference from Example 1 is that the amount of aluminum sulfate added in step (3) is 1.5 times the SiO2 content in the SiO2 micropowder.
[0054] Add 190 mL of 2 mol L -1 NaOH aqueous solution, stirred at 70 ° C for 300 min to obtain a sodium polysilicate solution; -1 The pH value of the sodium polysilicate solution was adjusted to 3.5 with an aqueous solution of sulfuric acid and then stirred at 50°C at a stirring speed of 350 rpm for 90 minutes to completely convert it into silicic acid and activate the silicic acid. Finally, it was kept at a constant temperature of 50°C for 2 hours to allow the activated silicic acid to gradually polymerize to obtain a polysilicate solution; 14.25 g of aluminum sulfate was added to the polysilicate solution and stirred for 20 minutes to mix it evenly, and then the pH value was adjusted to 1.6 and aged for 3 hours to obtain a polysilicate aluminum flocculant; 9.5 g of CaO was added to the polysilicate aluminum flocculant and stirred for 2 minutes to mix it evenly to obtain a calcium-based composite flocculant.
[0055] Example 6
[0056] The difference from Example 1 is that the amount of aluminum sulfate added in step (3) is 0.5 times the SiO2 content in the SiO2 micropowder.
[0057] Add 190 mL of 2 mol L -1 NaOH aqueous solution, stirred at 70 ° C for 300 min to obtain a sodium polysilicate solution; -1The pH value of the sodium polysilicate solution was adjusted to 3.5 with an aqueous solution of sulfuric acid and then stirred at 50°C at a stirring speed of 350 rpm for 90 minutes to completely convert it into silicic acid and activate the silicic acid. Finally, it was kept at a constant temperature of 50°C for 2 hours to allow the activated silicic acid to gradually polymerize to obtain a polysilicate solution; 4.75 g of aluminum sulfate was added to the polysilicate solution and stirred for 20 minutes to mix it evenly, and then the pH value was adjusted to 1.6 and aged for 3 hours to obtain a polysilicate aluminum flocculant; 9.5 g of CaO was added to the polysilicate aluminum flocculant and stirred for 2 minutes to mix it evenly to obtain a calcium-based composite flocculant.
[0058] The calcium-based composite flocculant prepared in this example was subjected to FTIR testing, and the results are shown in Figure 1 .
[0059] Example 7
[0060] The difference from Example 1 is that the amount of aluminum sulfate added in step (3) is 4.5 times the SiO2 content in the SiO2 micropowder.
[0061] Add 190 mL of 2 mol L -1 NaOH aqueous solution, stirred at 70 ° C for 300 min to obtain a sodium polysilicate solution; -1 The pH value of the sodium polysilicate solution was adjusted to 3.5 with an aqueous solution of sulfuric acid and then stirred at 50°C at a stirring speed of 350 rpm for 90 minutes to completely convert it into silicic acid and activate the silicic acid. Finally, it was kept at a constant temperature of 50°C for 2 hours to allow the activated silicic acid to gradually polymerize to obtain a polysilicate solution; 42.75 g of aluminum sulfate was added to the polysilicate solution and stirred for 20 minutes to mix it evenly, and then the pH value was adjusted to 1.6 and aged for 3 hours to obtain a polysilicate aluminum flocculant; 9.5 g of CaO was added to the polysilicate aluminum flocculant and stirred for 2 minutes to mix it evenly to obtain a calcium-based composite flocculant.
[0062] The calcium-based composite flocculant prepared in this example was subjected to FTIR testing, and the results are shown in Figure 1 .
[0063] Example 8
[0064] The difference from Example 1 is that the pH value is matured to 3.2.
[0065] Add 190 mL of 2 mol L -1 NaOH aqueous solution, stirred at 70 ° C for 300 min to obtain a sodium polysilicate solution; -1The pH value of the sodium polysilicate solution was adjusted to 3.2 with an aqueous solution of sulfuric acid and then stirred at 50°C at a stirring speed of 350 rpm for 90 minutes to completely convert it into silicic acid and activate the silicic acid. Finally, it was kept at a constant temperature of 50°C for 2 hours to allow the activated silicic acid to gradually polymerize to obtain a polysilicate solution; 23.75 g of aluminum sulfate was added to the polysilicate solution and stirred for 20 minutes to mix it evenly, and then the pH value was adjusted to 1.6 and aged for 3 hours to obtain a polysilicate aluminum flocculant; 9.5 g of CaO was added to the polysilicate aluminum flocculant and stirred for 2 minutes to mix it evenly to obtain a calcium-based composite flocculant.
[0066] Example 9
[0067] The difference from Example 1 is that the pH value is matured to 2.0.
[0068] Add 190 mL of 2 mol L -1 NaOH aqueous solution, stirred at 70 ° C for 300 min to obtain a sodium polysilicate solution; -1 The pH value of the sodium polysilicate solution was adjusted to 2.0 with an aqueous solution of sulfuric acid and then stirred at 50°C at a stirring speed of 350 rpm for 90 minutes to completely convert it into silicic acid and activate the silicic acid. Finally, it was kept at a constant temperature of 50°C for 2 hours to allow the activated silicic acid to gradually polymerize to obtain a polysilicate solution; 23.75 g of aluminum sulfate was added to the polysilicate solution and stirred for 20 minutes to mix it evenly, and then the pH value was adjusted to 1.6 and aged for 3 hours to obtain a polysilicate aluminum flocculant; 9.5 g of CaO was added to the polysilicate aluminum flocculant and stirred for 2 minutes to mix it evenly to obtain a calcium-based composite flocculant.
[0069] Example 10
[0070] The difference from Example 1 is that the activation time in step (2) is 60 min.
[0071] Add 190 mL of 2 mol L -1 NaOH aqueous solution, stirred at 70 ° C for 300 min to obtain a sodium polysilicate solution; -1The pH value of the sodium polysilicate solution was adjusted to 3.5 with an aqueous solution of sulfuric acid and then stirred at 50°C at a stirring speed of 350 rpm for 60 minutes to completely convert it into silicic acid and activate the silicic acid. Finally, it was kept at a constant temperature of 50°C for 2 hours to allow the activated silicic acid to gradually polymerize to obtain a polysilicate solution; 23.75 g of aluminum sulfate was added to the polysilicate solution and stirred for 20 minutes to mix it evenly, and then the pH value was adjusted to 1.6 and aged for 3 hours to obtain a polysilicate aluminum flocculant; 9.5 g of CaO was added to the polysilicate aluminum flocculant and stirred for 2 minutes to mix it evenly to obtain a calcium-based composite flocculant.
[0072] Embodiment 11
[0073] The difference from Example 1 is that the content of SiO2 micropowder is different, which is 90wt%, the impurities are different, and the particle size is different.
[0074] Add 190 mL of 2 mol L -1 NaOH aqueous solution, stirred at 70 ° C for 300 min to obtain a sodium polysilicate solution; -1 The pH value of the sodium polysilicate solution was adjusted to 3.5 with an aqueous solution of sulfuric acid and then stirred at 50°C at a stirring speed of 350 rpm for 90 minutes to completely convert it into silicic acid and activate the silicic acid. Finally, it was kept at a constant temperature of 50°C for 2 hours to allow the activated silicic acid to gradually polymerize to obtain a polysilicate solution; 22.5 g of aluminum sulfate was added to the polysilicate solution and stirred for 20 minutes to mix it evenly, and then the pH value was adjusted to 1.6 and aged for 3 hours to obtain a polysilicate aluminum flocculant; 9 g of CaO was added to the polysilicate aluminum flocculant and stirred for 2 minutes to mix it evenly to obtain a calcium-based composite flocculant.
[0075] Example 12
[0076] The difference from Example 1 is that the content of SiO2 micropowder is different, which is 99wt%, the impurities are different, and the particle size is different.
[0077] Add 190 mL of 2 mol L -1 NaOH aqueous solution, stirred at 70 ° C for 300 min to obtain a sodium polysilicate solution; -1The pH value of the sodium polysilicate solution was adjusted to 3.5 with an aqueous solution of sulfuric acid and then stirred at 50°C at a stirring speed of 350 rpm for 90 minutes to completely convert it into silicic acid and activate the silicic acid. Finally, it was kept at a constant temperature of 50°C for 2 hours to allow the activated silicic acid to gradually polymerize to obtain a polysilicate solution; 24.75 g of aluminum sulfate was added to the polysilicate solution and stirred for 20 minutes to mix it evenly, and then the pH value was adjusted to 1.6 and aged for 3 hours to obtain a polysilicate aluminum flocculant; 9.9 g of CaO was added to the polysilicate aluminum flocculant and stirred for 2 minutes to mix it evenly to obtain a calcium-based composite flocculant.
[0078] Comparative Example 1
[0079] Add 190 mL of 2 mol L -1 NaOH aqueous solution, stirred at 70 ° C for 300 min to obtain a sodium polysilicate solution; -1 The pH value of the sodium polysilicate solution was adjusted to 3.5 with an aqueous solution of sulfuric acid and then stirred at 50°C at a stirring speed of 350 rpm for 90 minutes to completely convert it into silicic acid and activate the silicic acid. Finally, it was kept at a constant temperature of 50°C for 2 hours to allow the activated silicic acid to gradually polymerize to obtain a polysilicate solution; 23.75 g of aluminum sulfate was added to the polysilicate solution and stirred for 20 minutes to mix it evenly, and then the pH value was adjusted to 1.6 and aged for 3 hours to obtain a polysilicate aluminum flocculant; 9.5 g of CaCl2 was added to the polysilicate aluminum flocculant and stirred for 2 minutes to mix it evenly to obtain a calcium-based composite flocculant.
[0080] Comparative Example 2
[0081] Add 190 mL of 2 mol L -1 NaOH aqueous solution, stirred at 70 ° C for 300 min to obtain a sodium polysilicate solution; -1 The pH value of the sodium polysilicate solution was adjusted to 3.5 with an aqueous solution of sulfuric acid and then aged. The solution was then stirred at 50°C at a stirring speed of 350 rpm for 90 min to completely convert it into silicic acid and activate the silicic acid. Finally, the solution was kept at a constant temperature of 50°C for 2 h to allow the activated silicic acid to gradually polymerize to obtain a polysilicate solution. 23.75 g of aluminum sulfate was added to the polysilicate solution and stirred for 20 min to mix it evenly. The pH value was then adjusted to 1.6 and aged for 3 h to obtain a polysilicate aluminum flocculant.
[0082] The flocculants obtained in the above examples and comparative examples were respectively subjected to COD, Fe 3+ , nano oil droplet removal experiment, and the obtained data are recorded in Table 1.
[0083] It should be further explained that the wastewater used in the test process is from the same batch. The test process includes: taking the same amount of flocculants prepared in the above embodiment and comparative example and applying them to the same amount of wastewater, respectively, and carrying out flocculation reaction at a stirring speed of 350 rpm for 24 hours. Then, the COD and Fe 3+ , nano oil droplet content, and then calculate their removal rates respectively. The calculation formula is: s = (c 未处理 -c 处理后 ) / c 未处理 , where c 未处理 is the content of the above-mentioned pollutants in the untreated sample, c 处理后 It is the content of one of the above pollutants in the treated sample.
[0084] The determination of COD was carried out with ferroxine as an indicator; the determination of nano-oil droplet content was carried out with ultraviolet calibration method; the determination of Fe 3+ The concentration was determined by the o-phenanthroline spectrophotometric method. 3+ The ion concentration was detected, where Fe 3+ Concentration standard curve, such as Figure 3 As shown, the Fe content in the solution can be accurately measured according to the standard curve. 3+ concentration.
[0085] Table 1
[0086] COD reduction rate (%) <![CDATA[Fe 3+ Removal rate (%)]]> Removal rate of nano-oil droplets (%) Example 1 84.2 94 90 Example 2 82.6 88 84 Example 3 80.5 89 87 Example 4 83.1 93 88 Example 5 80.2 87 83 Example 6 78.0 75 78 Example 7 79.3 80 75 Example 8 83.6 90 86 Example 9 77.5 92 79 Example 10 77.8 72 74 Embodiment 11 81.1 87 83 Example 12 80.8 86 85 Comparative Example 1 68.6 70 72 Comparative Example 2 60.5 58 65
[0087] It can be seen from the data in the table that the calcium-based composite flocculant prepared by the preparation method of the present invention has an effective effect on COD, Fe 3+ The nano-oil droplets have good removal effects. The removal rate of COD in wastewater can reach more than 77.5%, and the removal rate of nano-oil droplets in wastewater can reach more than 74%. 3+ The removal rate can reach over 72%.
[0088] Practical Application of Calcium-based Composite Flocculants
[0089] The calcium-based composite flocculant obtained in Example 1 was selected for scale-up application, and was specifically applied to factory sewage treatment. The specific method of use was: 75 mg L -1 The calcium-based flocculant compound is added and mixed with the factory sewage and stirred thoroughly. After flotation, the scum is removed. The COD amount of the water before sewage treatment and the COD amount of the water after sewage treatment are measured, recorded and made into a line graph, see Figure 2 , and continued to test 16 batches of samples with different COD amounts.
[0090] Depend on Figure 2 It can be seen that after the calcium-based composite flocculant prepared in Example 1 of the present invention is used to remove the factory sewage, there is a significant difference between the COD amount of the effluent and the COD amount of the effluent before the sewage treatment, and the COD amount of the effluent is significantly reduced compared with the COD amount of the influent. In particular, in the second batch, when the COD concentration of the sewage influent was 73mg / L, the COD removal rate could reach 61.6%; in the third batch, when the COD concentration of the sewage influent was 45mg / L, the COD removal rate could reach 73.3%; in the 12th batch, when the COD concentration of the sewage influent was 52mg / L, the COD removal rate could reach 90.9%; in the 15th batch, when the COD concentration of the sewage influent was 43mg / L, the COD removal rate could reach 76.7%. It can be seen that the calcium-based composite flocculant prepared by the method of the present invention has a good removal effect in actual application even for factory sewage with large differences in COD amounts and more complex sewage components, and the best effect can even reach 90.9%, which has good application prospects.
[0091] In addition, the present invention also selected Example 1, Example 6, and Example 7, and conducted FIIR test on the calcium-based composite flocculants prepared therefrom to determine their degree of polymerization. The results are shown in FIG. Figure 1 . In the picture, 462.25cm -1 is the bending vibration absorption peak of Al-O, 619.15cm -1 It is the characteristic peak of Si-OH-Al, 661.05cm -1 The peak is caused by Si-O, 1041.73cm -1 Symmetrical stretching vibration of Si-O-Al, 1159.22 cm -1 SO4 2- and HSO4 - The characteristic absorption peak is 1216.05cm -1 is the stretching vibration of Al-O-Al, 1642.45cm -1 Indicates the bending vibration caused by the HOH group in the water molecules contained in or adsorbed by the sample; 3300~3500cm -1 The water absorbed by -OH bending and stretching vibrations are all strong peaks. It can be seen that the calcium-based flocculant composite product prepared by the preparation method has a high degree of polymerization and a high yield rate.
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a calcium-based composite flocculant based on SiO2 micropowder, characterized in that: The preparation method comprises the following steps: Step (1), adding an inorganic strong alkali aqueous solution to SiO2 micropowder, heating and reacting, to obtain a polysilicate solution; wherein the SiO2 micropowder is SiO2 micropowder solid waste; Step (2), subjecting the polysilicate solution to aging, activation, and constant temperature standing to obtain a polysilicate solution; Step (3), adding aluminum sulfate to the polysilicic acid solution and stirring and mixing, and then adjusting the pH and aging to obtain a polysilicic acid aluminum flocculant; Step (4), adding CaO to the polyaluminum silicate flocculant to obtain the calcium-based composite flocculant.
2. The method for preparing a calcium-based composite flocculant based on SiO2 micropowder according to claim 1, characterized in that: The SiO2 content in the SiO2 fine powder solid waste is 90-99wt%; preferably, the particle size of the SiO2 fine powder is 0.1-150μm.
3. The method for preparing a calcium-based composite flocculant based on SiO2 micropowder according to claim 1, characterized in that: In terms of weight ratio, the amount of CaO added in step (4) is 1 to 1.3 times the SiO2 content in the SiO2 powder; Preferably, the amount of aluminum sulfate added in step (3) is 1.5 to 3 times the SiO2 content in the SiO2 micropowder by weight; More preferably, the amount of aluminum sulfate added in step (3) is 2 to 3 times the SiO2 content in the SiO2 micropowder, by weight ratio.
4. The method for preparing a calcium-based composite flocculant based on SiO2 micropowder according to claim 1, characterized in that: The inorganic strong alkali aqueous solution is an aqueous solution of NaOH and / or KOH; Preferably, the concentration of the inorganic strong alkali aqueous solution is 1 to 2 mol / L; Preferably, the molar amount of the inorganic strong base in step (1) is 1 to 3 times the molar amount of SiO2 in the SiO2 micropowder; Preferably, the temperature of the heating reaction in step (1) is 70-75° C. and the time is 150-300 min.
5. The method for preparing a calcium-based composite flocculant based on SiO2 micropowder according to any one of claims 1 to 4, characterized in that: The aging in step (2) is achieved by adding a strong inorganic acid to the polysilicate solution to adjust the pH; Preferably, the inorganic strong acid is sulfuric acid and / or hydrochloric acid; Preferably, the concentration of the inorganic strong acid is 1 to 4 mol / L; Preferably, the pH is adjusted to 2.5-4.0 during the aging operation; more preferably, the pH is adjusted to 3.2-3.5 during the aging operation.
6. The method for preparing a calcium-based composite flocculant based on SiO2 micropowder according to any one of claims 1 to 4, characterized in that: The activation operation is achieved by heating and stirring the matured polysilicate solution; Preferably, during the activation, the heating temperature is 40-60°C, the time is 70-100 min, and the stirring speed is 300-350 rpm; More preferably, the activation time is 85 to 95 minutes.
7. The method for preparing a calcium-based composite flocculant based on SiO2 micropowder according to any one of claims 1 to 4, characterized in that: The constant temperature standing temperature in the step (2) is 40 to 60° C., and the time is 1.5 to 2.5 hours.
8. The method for preparing a calcium-based composite flocculant based on SiO2 micropowder according to any one of claims 1 to 7, characterized in that: The stirring time after adding the aluminum sulfate in step (3) is 20 to 30 minutes; Preferably, in step (3), the pH is adjusted to 1.6 to 1.7; Preferably, the aging time in step (3) is 2.5 to 3.5 hours; Preferably, the stirring time after adding the CaO in step (4) is 2 to 4 minutes.
9. A calcium-based composite flocculant based on SiO2 micropowder, characterized in that: The calcium-based composite flocculant based on SiO2 micropowder is prepared according to the preparation method according to any one of claims 1 to 8.
10. An application of a calcium-based composite flocculant based on SiO2 micropowder, characterized in that: The calcium-based flocculant is prepared by the preparation method according to any one of claims 1 to 8, and the calcium-based composite flocculant is used to purify wastewater.
Citation Information
Patent Citations
Method for preparing polymer calcium-aluminum silicate coagulant from carbide slag
CN102092828A
Preparation method and application method of silicon dioxide cluster-based novel settling agent
CN108249532A
Production process of compound flocculating agent polysilicate aluminum ferric carrying positive charges
CN108529723A
Method for preparing aluminum oxide and silicon-calcium-potassium soil conditioner from high-alumina fly ash and aluminum oxide and silicon-calcium-potassium soil conditioner
CN117023615A
Process for producing polyaluminum chloride flocculant by using aluminum chloride wastewater as byproduct
CN117023840A
